2016
DOI: 10.1038/modpathol.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

A protein and mRNA expression-based classification of gastric cancer

Abstract: The overall survival of gastric carcinoma patients remains poor despite improved control over known risk factors and surveillance. This highlights the need for new classifications, driven towards identification of potential therapeutic targets. Using sophisticated molecular technologies and analysis, three groups recently provided genetic and epigenetic molecular classifications of gastric cancer (The Cancer Genome Atlas, 'Singapore-Duke' study, and Asian Cancer Research Group). Suggested by these classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
161
4
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(198 citation statements)
references
References 59 publications
25
161
4
8
Order By: Relevance
“…their tumors into more than four groups [24,25]. This approach expands on that of TCGA and similarly may have future therapeutic and prognostic implications.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…their tumors into more than four groups [24,25]. This approach expands on that of TCGA and similarly may have future therapeutic and prognostic implications.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The APC (adenomatous polyposis coli) is a tumor suppressor gene coding for a regulator of the Wnt pathway and has many tasks like labeling β-catenin for degradation [62]. Loss of the C terminus of APC can induce CIN in CRC, making it a prominent factor involved in chromosomal stability [63]. Dunican et al reported that PLK, CCNA2 , and RanBP2 are overexpressed in CIN-type CRC and claimed them to be a tool for separating CIN-type from MSI-type cancers [64].…”
Section: Cin Occurrence In Various Cancersmentioning
confidence: 99%
“…It was suggested that p53 aberrant GCs incline toward higher HER2/neu expression, and the potential targeting molecules can be HER2, EGFR, VEGFR, MET, FGFR2, and cell cycle mediators (CCNE1, CCND1, and CDK6), which were all overexpressed. Oppositely, the p53 normal group had a high MUC6 expression and had been defined as the subtype with expression of normal gastric mucosa genes [63].…”
Section: Gc Classificationmentioning
confidence: 99%
“…However, other GCs are heterogeneous. Recent studies have proposed that additional markers, including epithelial-mesenchymal transition (EMT) features and TP53 mutations, could be used for further molecular classification [17, 18], although little is known about these categories from a tumor microenvironment-related perspective.…”
Section: Introductionmentioning
confidence: 99%